Comparison of Laws Related to the Copyright of Visual Artworks Based on Generative AI (Artificial Intelligence) Reviewed from Indonesian and UK Laws - Rizki Pratama, Muh Ersandi; Hafiidz Syam, Syahrul (Trunojoyo Madura University, 2024)
AI has demonstrated its limitless potential in bringing innovation and increasing efficiency. However, this raises new problems regarding the status of Generative AI-based works of art, where the work is the result of data processing from AI technology. The way AI works, which uses creations as input data to produce music, articles and paintings, can open up the potential for rights violations. copyright because its exclusive use is protected from being duplicated or used for profit (commercial) and raises a question regarding the ownership status of Generative AI-based painting works of art. Another consideration in providing ownership status protection for Generative AI-based works of art is the possibility of copyright infringement. The method used in compiling this research is research with a normative juridical method approach. The approaches used are the conceptual approach, comparative approach and statutory approach. Authenticity is very important in copyright protection. In Indonesia, copyright protection is regulated in Law Number 28 of 2014 concerning Copyright, article 1 numbers 1 and 2 do not clearly explain the authenticity of a work, from the definition of the creator and creation, there are elements that become limitations or benchmarks, namely elements independent creation (independent creation). CDPA 1988, or the Copyright, Designs and Patents Act 1988, is the copyright law applicable in the United Kingdom. This law is an important legal framework for copyright protection in the country. The 1988 CDPA provides copyright protection for created works, this Act further defines computer-generated works.